Immediate Implant Placement and Provisionalization in the Esthetic Zone: A 6.5-Year Follow-Up and Literature Review - Hsiu-Wan Meng; Esther Yun Chien; Hua-Hong Chien (Case Reports in Dentistry)
The success of dental implant therapy in the esthetic zone requires not only functional osseointegration but also a satisfactory esthetic outcome. To establish harmony, balance, and continuity of gingival architecture between an implant restoration and the adjacent natural dentition is challenging. Immediate implant placement and provisionalization following tooth extraction have been documented as a predictable treatment modality, with fewer surgical interventions needed, to replace a missing tooth in the esthetic zone. This case report illustrates immediate implant placement and provisionalization to replace a failing maxillary right central incisor while maintaining optimal gingival esthetics. The maxillary right central incisor was extracted without flap elevation to minimize soft and hard tissue trauma. Immediately afterwards, the implant was installed using a surgical stent and restored with a provisional crown that had no occlusal contacts. During healing, no significant adverse effects were observed clinically or radiographically. This proposed treatment modality provided the patient with immediate esthetics, function, and comfort without any complications during a follow-up period of 6.5 years.